2017
DOI: 10.1177/2047487317737629
|View full text |Cite
|
Sign up to set email alerts
|

Sauna exposure leads to improved arterial compliance: Findings from a non-randomised experimental study

Abstract: Background Heat therapy has been suggested to improve cardiovascular function. However, the effects of hot sauna exposure on arterial compliance and the dynamics of blood flow and pressure have not been well documented. Thus, we investigated the short-term effects of sauna bathing on arterial stiffness and haemodynamics. Design The design was an experimental non-randomised study. Methods There were 102 asymptomatic participants (mean age, 51.9 years) who had at least one cardiovascular risk factor. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 43 publications
2
59
0
Order By: Relevance
“…4 Sauna bathing habits may have changed over time, but still a typical Finnish person has a sauna bath at least once per week, with the average habitual frequency being 2 to 3 times/wk. [5][6][7] During a sauna session, the heart rate may increase from baseline up to 120 to 150 beats/ min. There is no active function of skeletal muscles during sauna bathing, which is in contrast to the training response experienced during physical activity.…”
Section: Sauna Bathingmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Sauna bathing habits may have changed over time, but still a typical Finnish person has a sauna bath at least once per week, with the average habitual frequency being 2 to 3 times/wk. [5][6][7] During a sauna session, the heart rate may increase from baseline up to 120 to 150 beats/ min. There is no active function of skeletal muscles during sauna bathing, which is in contrast to the training response experienced during physical activity.…”
Section: Sauna Bathingmentioning
confidence: 99%
“…Evidence suggests that the responses produced by an ordinary sauna bath correspond to those produced by moderateor high-intensity physical activity such as walking. 32 Pathways implicated in the effects of sauna bathing on vascular disease and mortality risk include reduction in systemic BP 14 ; improvement in endothelial function [33][34][35] ; reduction in oxidative stress 36,37 and inflammation 38,39 ; beneficial modulation of the autonomic nervous system 11 ; positive alteration in levels of circulating vascular risk factors such as natriuretic peptides 40 and lipids 41,42 ; hormonal changes; improved arterial stiffness, arterial compliance, and intima media thickness 7,36,40,43,44 ; and improvement in the cardiorespiratory system 45 as well as cardiovascular function 3,4,46 (Figure 2). Indeed, these pathways are involved in the pathophysiology of chronic disease outcomes such as type 2 diabetes and CVD as well as mortality.…”
Section: Pathways Implicated In Health Benefits Of Sauna Bathingmentioning
confidence: 99%
“…9 Sauna bathing, a traditional Finnish activity which is commonly used for the purposes of pleasure, relaxation, and wellness, and becoming a popular activity in many other countries, 12,13 has been observed to be linked to several health benefits. These include improvement in the pain and symptoms associated with musculoskeletal diseases 14 ; treatment of chronic headache 15 ; improvement in CV function 16,17 and reduced risk of respiratory diseases, 18,19 hypertension, 20 and neurocognitive disease. 21 Recent long-term observational epidemiological evidence has shown that having frequent sauna baths is independently associated with a reduced risk of SCD.…”
mentioning
confidence: 99%
“…Pulse wave velocity (PWV) and augmentation index (AIx) as measures of arterial stiffness were measured before, immediately after, and 10 min after the maximal graded exercise test by a single trained researcher (EL) using a PulsePen device (DiaTecne s.r.l., Milan, Italy; http://www.pulsepen.com) which includes one tonometer and an integrated ECG unit (Lee et al., 2018, 2019). The measurement of arterial stiffness and arterial dilatation capacity followed closely established guidelines (Tomlinson, 2012; Van Bortel et al., 2012).…”
Section: Methodsmentioning
confidence: 99%